(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted the problems of legal regulation of subsoil use. The proposals on reforming the system of state regulation of subsoil use are given. These measures are aimed at ensuring effective use of subsoil. It is important to note topicality the main aspects in the development of legislation on the subsoil in modern conditions, also touches upon the issues of rational subsoil use and state management in the sphere of subsoil protection and subsoil use. This article contains the objectives and principles of the Kazakhstani Code on Subsoil and Subsoil use, that has entered in force at the end of June 2018. This Code is designed to simplify regulation of mining, hydrocarbons and uranium industries, to increase attractiveness of them for investors and to allow open access to geological data. Analysis of the legislation on subsoil, leads to the fact that today the state, being the sole owner, provides guarantees of protection and optimal use of subsoil. Sub-soil resources, i.e., mineral and petrochemical resources, are exhaustible deposits, and the potential depletion of these deposits is therefore of social concern. The issue is to assess the real value of one unit of resource, i.e., the burden for society of not having it in the future, or in a less usable form, due to its present consumption. It is particularly significant when making decision about renewable energy, waste recycling, and the use of new technologies that use sub-soil resources. Key words: subsoil resources, legislation, rational use, state, rights to subsoil resources, state regulation.